A Systematic Review of Economic Decision Analytic Models in Care Home Populations - Prasertwachirakul, Phornchai (Journal of Health Science of Thailand, 2019)
Healthcare costs of the elderly are expected to escalate as a result of population aging. Parti-cularly those of the care home populations who usually be frailer than general elderly. Therefore, it is crucially important to allocate healthcare resources efficiently among this particular population by using cost-effectiveness evidence from economic decision analytic models. The objectives of this study were to evaluate the cost-effectiveness evidence of each healthcare intervention from published economic decision analytic models with regards to the care home populations, and to assess the quality of those economic decision analytic models by using the Philips checklist. A systematic literature review of decision analytic models carried out with the care home populations was conducted. All previously published economic evaluations between January 2000 and June 2016 using decision analytic modeling method conducted within the setting of care homes were searched via electronic databases (MEDLINE/EMBASE). As a result, 1,559 studies were searched; and 15 studies met the criteria and were reviewed in depth. The 15 studies related to 4 clinical fields namely (1) fracture/fall prevention, (2) pressure ulcer prevention, (3) influenza treatment/prophylaxis, and (4) TB screening strategies. Nonetheless, according to the evidence, only 5 feasible interventions were found to be cost-effective and had potential for implementation in a wider context. In terms of quality assessment, a number of methodological issues relevant to structure, data and consistency were observed in most studies. In conclusions, according to this systematic literature review relevant to Thai healthcare context, the majority of these 5 cost-effective interventions have been implemented widely except for the hip protectors. The devices are barely used in Thailand in spite of the fact that the consistent evidence from this systematic review has suggested its cost-effectiveness apparently. Therefore, this could be an opportunity for Thailand in terms of implications of this device in future research and medical practice.